Lymphomatoid Papulosis Type A: A Case Report of the "Wait-and-See Strategy" in a 27-Year-Old Male Patient with Extensive Disease - Eirini Kavvalou; Maria Stefanidou; Sabine Elke Krueger-Krasagakis; George Evangelou; Dimitra Koumaki; Leonidas Marinos; Maria Tzardi; Konstantinos Krasagakis (Hindawi Limited, 2019)
This is the case of a 27-year-old male patient with a newly diagnosed extensive lymphomatoid papulosis type A involving cosmetically sensitive areas (e.g. face), who refused to be treated with a low dose of methotrexate, as recommended by the published literature. The natural course of the disease was proved to be strikingly satisfying though, with a complete regression of all skin lesions at the 4-week follow-up, including an ulcerated nodule 3 x 3 cm in dimension, which was expected to heal at least in months. We report this case to reconsider weighting the risks and the short-term benefits of methotrexate treatment, even in the case of an extensive disease.